2017
DOI: 10.1515/polyeng-2016-0272
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose modification and shaping – a review

Abstract: Abstract This review aims to present cellulose as a versatile resource for the production of a variety of materials, other than pulp and paper. These products include fibers, nonwovens, films, composites, and novel derivatized materials. This article will briefly introduce the structure of cellulose and some common cellulose derivatives, as well as the formation of cellulosic materials in the micro- and nanoscale range. The challenge with dissolution of cellulose will be discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 115 publications
(54 reference statements)
0
66
0
2
Order By: Relevance
“…However, numerous other pathways for cellulose modification have been reviewed by others. 44,45 A hierarchical cell wall structure is the basis of cellulose fibers, microcrystalline and microfibrillated celluloses (MCC and MFC, respectively), nanofibrils (CNF), and nanocrystals (CNC). Preparation of MCC, MFC, CNF, and CNC involves breaking down the hierarchy into individualized micro-or nanostructures with high crystallinity, therefore reducing the amount of amorphous material present.…”
Section: Cellulosementioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous other pathways for cellulose modification have been reviewed by others. 44,45 A hierarchical cell wall structure is the basis of cellulose fibers, microcrystalline and microfibrillated celluloses (MCC and MFC, respectively), nanofibrils (CNF), and nanocrystals (CNC). Preparation of MCC, MFC, CNF, and CNC involves breaking down the hierarchy into individualized micro-or nanostructures with high crystallinity, therefore reducing the amount of amorphous material present.…”
Section: Cellulosementioning
confidence: 99%
“…Cellulose derivatives are attractive as hydrocolloids since the fact that they are produced by chemical modification of cellulose ensures that they have uniform properties. 69 Numerous methods for cellulose modification have been explored, 44,45 but the most common methods for producing emulsion stabilizers are the etherification reactions of cellulose into MC, HPC, HPMC, MEC, and CMC ( Fig. 3).…”
Section: Amphiphilic Surfactantsmentioning
confidence: 99%
“…Hence, the second priority should be the separation and use of primary components of lignocellulose (cellulose, lignin). This can be with or without structural or chemical modification before or after dissolution, leading to functional polymers . These materials can possess the required physical and chemical properties for making consumable products for daily use .…”
Section: Road Map For Gainful Utilization Of Agricultural Wastementioning
confidence: 99%
“…The modification of biopolymers such as cellulose, lignin, and chitosan is therefore a key research area for both academic‐ and industry‐related fields . A great variety of modification techniques have been used to bring new functionalities into these materials, leading to applications in packaging, adhesives, biomedicine, building materials, or composites . In recent years, the interest for new materials based on bulk lignocellulosics (i.e., wood) has raised .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A great variety of modification techniques have been used to bring new functionalities into these materials, leading to applications in packaging, adhesives, biomedicine, building materials, or composites. 2,[4][5][6][7][8] In recent years, the interest for new materials based on bulk lignocellulosics (i.e., wood) has raised. [9][10][11][12][13][14][15][16][17] Although wood has been and still is mainly used in the furniture and construction sector, recent studies have shown its potential in a wide variety of applications going beyond its classical utilizations.…”
mentioning
confidence: 99%